A contemporary presentation of the incidence and management of spontaneous coronary artery dissection (SCAD) in New Zealand: an ANZACS-QI study. (14th October 2021) - Mbizvo, R M; Alfadhel, M; Williams, M J A; Coffey, S; Kerr, A; Webster, M; Lee, M
Abstract: Background/Purpose: Spontaneous coronary artery dissection (SCAD) is an underdiagnosed and poorly understood condition that frequently affects younger women without cardiovascular risk factors. In this project we aimed to describe the present landscape of SCAD in New Zealand (NZ). Methods: All patients in NZ who were admitted to hospital with a diagnosis of Acute Coronary Syndrome (ACS) from July 2019 to December 2020 and underwent coronary angiography were identified from the All NZ Coronary Syndrome Quality Imporvment (ANZACS-QI) registry. Results: Of 12, 053 patients admitted to hospital with an ACS, 122 had SCAD (1.0%). 80% of those with SCAD were female, with mean age of 57 years, and fewer traditional cardiovascular risk factors. Non-ST elevation myocardial infarction was the most common presentation (82.0%), while 16.4% presented with ST elevation myocardial infarction. The majority of patients were managed conservatively (91.8%) while 8.2% underwent PCI. 56.6% of SCAD patients had normal LV function. Nearly 80% of patients were discharged on Acetylsalicylic acid (ASA) therapy, while 60.7% had a P2Y12 inhibitor. Beta blockers, Statins and ACEI/ARB were part of the management strategy in 62.5%, 59.8% and 42.6% of patients respectively while 47.5% had a combination of all 3. Amongst 122 patients, only 1 in-hospital death and 1 inpatient recurrent MI occurred, with 3 patients having bleeding of any kind. Conclusion: In NZ, incidence of SCAD is approximately 1%. Most patients affected in NZ are female with fewer traditional cardiovascular risk factors. Management is predominantly conservative, and there is a low rate of early adverse outcomes. Funding Acknowledgement: Type of funding sources: None.